Setor informal: um estudo sobre os camelôs do Shopping Popular em Cuiabá - MT/2003 - Silva, Rosana Aparecida de Andrade (2003)
The phenomenon of the informality has been common in the quarrels that involve Sciences Social and Human. First for not corresponding to a temporary and isolated phenomenon, and on the other hand for dealing with a presente situation in the majority of the Brazilian urban centers. In Cuiabá municipality, the alternative commerce appears as a social answer to the problems caused for the economic crisis of the country and seems to be deep-rooted to the urban landscape. This assignment angles was the street peddlers, in special that ones who develop their in a specific location on lowered of Cuiabá. Researches pretending to fill a blank of information about this subject involve theoritical and empirical levels. The theory searched to raise in a generalized manner given pertinent the informality and the pratical level through field research searched to analyze excellent aspects on the economic and occupational situation of a composed sample for two hundred and theree workers who develope the pratical one of the informal commerce in Shopping Popular in Cuiaba/MT. The analysis of gotten data alllowed to appreciate some excellent aspects with regard to the activity os the peddler, as: origni, formation, income, perspectives with regard to activity among others. In las analysis it still alllowed to verify the factors that condition the permanence these workers in this type of informal activity